Effects of palm oil mill effluent (POME) anaerobic sludge from 500 m3 of closed anaerobic methane digested tank on pressed-shredded empty fruit bunch (EFB) composting process - Samsu Baharuddin, Azhari; Lim, Siong Hock; Mohd Yusoff, Mohd Zulkhairi; Abdul Rahman, Nor'aini; Md. Shah, Umi Kalsom; Hassan, Mohd Ali; Wakisaka, Minato; Sakai, Kenji; Shirai, Yoshihito (Academic Journals, 2010)
In this study, co-composting of pressed-shredded empty fruit bunches (EFB) and palm oil mill effluent(POME) anaerobic sludge from 500 m3 closed anaerobic methane digested tank was carried out. High nitrogen and nutrients content were observed in the POME anaerobic sludge. The sludge was subjected to the pressed-shredded EFB to accelerate the co-composting treatment. In the present study, changes in the physicochemical characteristics of co-composting process were recorded and evaluated. The cocomposting treatment was completed in a short time within 40 days with a final C/N ratio of 12.4. The co-composting process exhibited a higher temperature (60 - 67°C) in the thermophilic phase followed by curing phase after four weeks of treatment. Meanwhile, pH of the composting pile (8.1 - 8.6) was almost constant during the process and moisture content was reduced from 64.5% (initial treatment) to 52.0% (final matured compost). The use of pressed-shredded EFB as a main carbon source and bulking agent contributed to the optimum oxygen level in the composting piles (10 - 15%). The biodegradation of composting materials is shown by the reduction of cellulose (34.0%) and hemicellulose (27.0%) content towards the end of treatment. In addition, considerable amount of nutrients and low level of heavy metals were detected in the final matured compost. It can be concluded that the addition of POME anaerobic sludge into the pressed-shredded EFB composting process could produce acceptable and consistent quality of compost product in a short time.